THE CHANGING STRUCTURE OF THE HIGH SCHOOL HISTORY CURRICULUM - Smith, David C. (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1976)
What stirred those involved in history teaching in 1960 was a fresh look at the school curriculum taken by Jerome Bruner. In his Process of Education, Bruner expounded upon two ideas that were to have a profound effect upon the teaching of history. One was that the fundamental ideas or principles in a discipline could be used as the basis for planning school curricula. The other was that curricula should he devised to develop skills in intuitive and analytical thinking.